1995
DOI: 10.1210/jcem.80.12.8530584
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal metabolism in patients with osteoporosis after discontinuation of long-term treatment with oral pamidronate.

Abstract: Bisphosphonates are used with increasing frequency in the treatment of patients with osteoporosis. Continuous administration of low doses of nitrogen-containing bisphosphonates by mouth is the preferred mode of therapy. The skeletal half-life of bisphosphonates is long, however, and little is known about their long term effects on skeletal metabolism. We examined the changes in biochemical parameters of bone turnover [serum alkaline phosphatase and urinary hydroxyproline (OHP)], in bone mineral density, and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…207,208 Recent studies of the use of pamidronate and alendronate have suggested, however, that bone loss may eventually resume at an accelerated rate. 209,210 Similar findings have been reported for risedronate. 211 The offset times for anabolic regimens have not been characterised but bone loss occurred shortly after stopping treatment with fluoride.…”
Section: Onset and Offset Of Actionsupporting
confidence: 84%
See 1 more Smart Citation
“…207,208 Recent studies of the use of pamidronate and alendronate have suggested, however, that bone loss may eventually resume at an accelerated rate. 209,210 Similar findings have been reported for risedronate. 211 The offset times for anabolic regimens have not been characterised but bone loss occurred shortly after stopping treatment with fluoride.…”
Section: Onset and Offset Of Actionsupporting
confidence: 84%
“…A meta-analysis of total cholesterol lowering in the setting of primary and secondary cardiovascular disease suggested that cardiac events decreased by 2% for every 1% reduction in serum cholesterol. 210 On this basis, in the sensitivity analysis it has been assumed that raloxifene might decrease cardiovascular risk by 20%.…”
Section: Sermsmentioning
confidence: 99%
“…[119,120,125] It is only knownt hat the process can occur and the released drugs are found to be active at the bone surface afresh. [143] Yet, subsequent pathways of BPs following their release are unknown. [39] Most likely,r eleaser eactions are also affected by the drug itselfa nd the properties of apatite.…”
Section: Synthetic Nanocrystalline Apatites and Naturalb One Mineralmentioning
confidence: 99%
“…The knowledge about releasing processes of BPs from the bone matrix is limited . It is only known that the process can occur and the released drugs are found to be active at the bone surface afresh . Yet, subsequent pathways of BPs following their release are unknown .…”
Section: Introductionmentioning
confidence: 99%